2012
DOI: 10.1038/mp.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

The ADHD-susceptibility gene lphn3.1 modulates dopaminergic neuron formation and locomotor activity during zebrafish development

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by inattention, hyperactivity, increased impulsivity and emotion dysregulation. Linkage analysis followed by fine-mapping identified variation in the gene coding for Latrophilin 3 (LPHN3), a putative adhesion-G protein-coupled receptor, as a risk factor for ADHD. In order to validate the link between LPHN3 and ADHD, and to understand the function of LPHN3 in the etiology of the disease, we examined its ortholog lphn3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
151
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(166 citation statements)
references
References 61 publications
(31 reference statements)
13
151
1
1
Order By: Relevance
“…Loss of function mutants, targeting the zebrafish LPHN homolog LPHN3.1, displayed impulsive motor phenotype and a reduction, as well as misplacement, of dopamine-positive neurons, pointing to a neurodevelopmental role of LPHN3 in affecting motility behaviors (106). Additionally, LPHN3 null mice studies revealed changes in mRNA-encoding transporters involved in the dopaminergic and serotonergic pathways in newborns and in the striatal levels of dopamine and serotonin in adulthood (1-7); C-tail, carboxy-terminal tail; PDZ bd, PDZ-binding domain.…”
Section: Attention-deficit Hyperactivity Disordermentioning
confidence: 98%
“…Loss of function mutants, targeting the zebrafish LPHN homolog LPHN3.1, displayed impulsive motor phenotype and a reduction, as well as misplacement, of dopamine-positive neurons, pointing to a neurodevelopmental role of LPHN3 in affecting motility behaviors (106). Additionally, LPHN3 null mice studies revealed changes in mRNA-encoding transporters involved in the dopaminergic and serotonergic pathways in newborns and in the striatal levels of dopamine and serotonin in adulthood (1-7); C-tail, carboxy-terminal tail; PDZ bd, PDZ-binding domain.…”
Section: Attention-deficit Hyperactivity Disordermentioning
confidence: 98%
“…For clarity, we have categorized genes in Tables 1–4 by the disorder to which they are most closely associated in the literature, noting overlapping associations where applicable, though studies of the biological functions of these genes are likely to be relevant across diagnostic boundaries. While zebrafish have also been used to study other neurodevelopmental disorders, including attention-deficit/hyperactivity disorder (ADHD; Lange et al, 2012a,b), Bardet-Biedl syndrome (BBS; Zaghloul et al, 2010; Heon et al, 2016; Lindstrand et al, 2016), and maple syrup urine disease (MSUD; Friedrich et al, 2012), we focus on ASD, epilepsy, ID and schizophrenia, which have been the subject of most zebrafish studies to date and highlight the advantages of this system for the functional analysis of risk genes. Moreover, while an increasing number of studies are investigating complex behaviors in adult zebrafish, such as social behaviors, it is important to observe that there are limitations of face validity, such that it is not possible to recapitulate fully the symptoms of neurodevelopmental disorders in zebrafish (or any animal model), and this is not a prerequisite for demonstrating the relevance of the model.…”
Section: Zebrafish Models Of Neurodevelopmental Disordersmentioning
confidence: 99%
“…This finding appears to contradict the notion that these dopaminergic neurons are truly homologous to the ascending dopaminergic system of other vertebrates as claimed earlier (Rink and Wullimann, 2001). Nevertheless, given the conserved organization of the basal ganglia proper, it seems likely that ascending dopaminergic neurons serve similar functions (Lange et al, 2012). Indeed, pharmacological and genetic experiments support this idea.…”
Section: Introductionmentioning
confidence: 99%